Size- Dependent Optical Properties Of Nanoparticles (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
The rapid development of nanotechnology requires a thorough understanding of the size-dependent optical properties of nanoparticles. In this study, the synthesis, size control, and optical characterization of gold (Au), silver (Ag) nanoparticles, and CdSe quantum dots were investigated. The results showed that the surface plasmon resonance (SPR) of Au nanoparticles shifted to longer wavelengths with increasing particle size, while Ag nanoparticles exhibited sharper and higher amplitude SPR peaks.These findings highlight the potential applications of nanoparticles in biosensing, bioimaging, photonics, energy conversion, and photothermal therapy.